Muscle damage and inflammation during recovery from exercise - Peake, J. M.; Neubauer, O.; Della Gatta, P. A.; Nosaka, K. (Journal of Applied Physiology, 2017)
Unaccustomed exercise consisting of eccentric (i.e., lengthening) muscle contractions often results in muscle damage characterized by ultrastructural alterations in muscle tissue, clinical signs, and symptoms (e.g., reduced muscle strength and range of motion, increased muscle soreness and swelling, efflux of myocellular proteins). The time course of recovery following exercise-induced muscle damage depends on the extent of initial muscle damage, which in turn is influenced by the intensity and duration of exercise, joint angle/muscle length, and muscle groups used during exercise. The effects of these factors on muscle strength, soreness, and swelling are well characterized. By contrast, much less is known about how they affect intramuscular inflammation and molecular aspects of muscle adaptation/remodeling. Although inflammation has historically been viewed as detrimental for recovery from exercise, it is now generally accepted that inflammatory responses, if tightly regulated, are integral to muscle repair and regeneration. Animal studies have revealed that various cell types, including neutrophils, macrophages, mast cells, eosinophils, CD8 and T-regulatory lymphocytes, fibro-adipogenic progenitors, and pericytes help to facilitate muscle tissue regeneration. However, more research is required to determine whether these cells respond to exercise-induced muscle damage. A large body of research has investigated the efficacy of physicotherapeutic, pharmacological, and nutritional interventions for reducing the signs and symptoms of exercise-induced muscle damage, with mixed results. More research is needed to examine if/how these treatments influence inflammation and muscle remodeling during recovery from exercise.